Cara the camp fairy - Meadows, Daisy (New York : Scholastic, 2011)
Because of Cara's special magic, campers can navigate through the woods, stay cool during the day, and do lots of fun activities, but Jack Frost has sent his goblins to steal that magic. Can Rachel and Kirsty help Cara fix things before the whole summer is ruined?
2.
006-009.
Keywords: Jack Frost -- (Legendary character) -- Juvenile fiction; Tate, Kirsty (Fictitious character) -- Juvenile fiction; Walker, Rachel (Fictitious character) -- Juvenile fiction; Fairies -- Juvenile fiction; Camps -- Juvenile fiction; Magic -- Juvenile fiction; Fantasy fiction; Tate, Kirsty (Fictitious character) -- Fiction; Walker, Rachel (Fictitious character) -- Fiction; Fairies -- Fiction; Camps -- Fiction; Magic -- Fiction; Fantasy; Tate, Kirsty (Fictitious character) -- Fiction; Walker, Rachel (Fictitious character) -- Fiction; Jack Frost -- Fiction; Fairies -- Fiction; Camps -- Fiction; Magic -- Fiction; Fantasy